2014
DOI: 10.1186/s12879-014-0563-7
|View full text |Cite
|
Sign up to set email alerts
|

In-house ELISA screening using a locally-isolated Leptospirain Malaysia: determination of its cut-off points

Abstract: BackgroundLeptospirosis is a zoonotic disease caused by Leptospira species and is distributed globally. Microscopic agglutination test (MAT) is the serological ‘gold standard’ for diagnosis of leptospirosis but it is time-consuming and labour-intensive. An alternative serological method that is rapid, sensitive and specific is important for early treatment to reduce morbidity and mortality. The use of local Leptospira isolation may improve the sensitivity and specificity of the test because it may varies from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Indeed, a previous study suggested a negative relationship between mammalian diversity and human incidence of leptospirosis in island ecosystems, which may be explained by both bioregulation and dilution effects 44 . To answer these questions, it will be necessary to improve current techniques for culturing Leptospira from field samples and to develop tests for Leptospira infection capable of detecting local host-associated Leptospira lineages 45 . Such investigations would allow for a greater understanding at the global level of the role of different host/reservoir species in human leptospirosis and the design of improved preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous study suggested a negative relationship between mammalian diversity and human incidence of leptospirosis in island ecosystems, which may be explained by both bioregulation and dilution effects 44 . To answer these questions, it will be necessary to improve current techniques for culturing Leptospira from field samples and to develop tests for Leptospira infection capable of detecting local host-associated Leptospira lineages 45 . Such investigations would allow for a greater understanding at the global level of the role of different host/reservoir species in human leptospirosis and the design of improved preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates obtained from three cattle, two dogs, and one environmental sample were closely related to L. kmetyi serovar Malaysia (Group 2) and L. yasudae (Group 3) ( Figure 2 ), with a mean genetic distance within group of 0.001 and 0.002, respectively ( Table 3 ). These animals could become infected with Leptospira because of constant exposure to contaminated soil, as L. kmetyi was mostly isolated from environmental samples [ 44 , 45 , 46 ]. In addition, a novel species, L. yasudae was also isolated from the soil of an ex-situ wild animal conservation area in Malaysia recently [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various ELISA tests, among others, have been described as serological tests complementary to MAT [70,[74][75][76]94,99]. Most commercially available ELISA tests detect immunoglobulin class M antibodies, which are critical for early diagnosis of acute infection and are often detectable before MAT becomes positive [75,76,78,98,100,101].…”
Section: Discussionmentioning
confidence: 99%